2021
DOI: 10.1111/cogs.12919
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Evidential Impact on Perceptual Probabilistic Judgments

Abstract: In a series of three behavioral experiments, we found a systematic distortion of probability judgments concerning elementary visual stimuli. Participants were briefly shown a set of figures that had two features (e.g., a geometric shape and a color) with two possible values each (e.g., triangle or circle and black or white). A figure was then drawn, and participants were informed about the value of one of its features (e.g., that the figure was a “circle”) and had to predict the value of the other feature (e.g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…The fact that Mangiarulo et al (2021) found an effect without structure while we didn't is informative. Besides seeing the distribution only quite briefly, their participants did not know, when looking at the distribution, what the evidence would be, or what dimension they would be asked about.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The fact that Mangiarulo et al (2021) found an effect without structure while we didn't is informative. Besides seeing the distribution only quite briefly, their participants did not know, when looking at the distribution, what the evidence would be, or what dimension they would be asked about.…”
Section: Discussionmentioning
confidence: 76%
“…It's interesting to note that an independent study (Mangiarulo et al, 2021), looking at effects of evidential impact on perceptual probabilistic judgment, found an effect of confirmation theory in a design that shares some properties with our flat condition. The experiment by Mangiarulo et al (2021) involved a two-step process. First, participants saw shuffled sets of about 30 elements of two possible shapes and two possible colors.…”
Section: Discussionmentioning
confidence: 83%
“…It varies across conditions the direction and evidential impact of the evidence, the causal status of the base-rate information, and the causal status of the evidence. This allows us to compare the merits of the Causal Bayesian Reasoner theory, the Evidential Impact Reasoner theory, and a third possibility, prompted by the suggestion that confirmation-theoretic reasoning strategies are triggered by a search for causal explanations of phenomena (Mangiarulo, Pighin, Polonio, & Tentori, 2021), as we detail shortly. Subjects were told to consider a fictional story about an ancient Mesopotamian village.…”
Section: Experiments Design and Materialsmentioning
confidence: 99%
“…These results are consistent with those from the category-based induction literature, according to which adults, and even children as young as 5, when evaluating argument strength, follow popular principles of evidential impact, such as the similarity between premises and conclusion and the diversity of premises (Heit and Hahn, 2001;Lo et al, 2002;Lopez et al, 1992;Osherson et al, 1990;Zhong et al, 2014). The spontaneous, and often implicit, appreciation of evidential impact has been shown, often under other names, to play a fundamental role in a variety of other higher-and lower-level cognitive processes, including causal induction (Cheng and Novick, 1990;Cheng, 1997), conditional reasoning (Douven and Verbrugge, 2012;Krzyzanowska et al, 2017), learning (Danks, 2003), language processing (Bhatia, 2017;Bullinaria and Levy, 2007;Nadalini et al, 2018;Paperno et al, 2014), and even perception (Mangiarulo et al, 2019).…”
Section: The Preeminence Of Impact Assessment Over Probability Judgmentsmentioning
confidence: 99%